If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13x + -37) = 41 Reorder the terms: (-37 + 13x) = 41 Remove parenthesis around (-37 + 13x) -37 + 13x = 41 Solving -37 + 13x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + 13x = 41 + 37 Combine like terms: -37 + 37 = 0 0 + 13x = 41 + 37 13x = 41 + 37 Combine like terms: 41 + 37 = 78 13x = 78 Divide each side by '13'. x = 6 Simplifying x = 6
| 18m-14=12m-2 | | 15=4+m | | 8m=6n-14 | | 2(-3x+3)+4x=-4 | | B=bru | | (5a+1)=(3a+27) | | 3x+10-5x-3=2x-3-10 | | 12x^2-12x+12xy-6y^2+84y+36=0 | | (2n-1)!/(n!) | | 0=6x+1x | | -2(-x+3)=18 | | X^2-3x=3x-9+9 | | -4n+1n=12 | | -2-3(2x+9)=-32 | | 3x+10+2x-3-10=5x-3 | | -8(7-2x)=40-8x | | y=-3*9.6+208 | | 4=1x+3x | | .04(5+2x)-.05=3(.03x+.07) | | -10+2(x+5)=-18 | | 54=a+48 | | 12x+15y = 105 | | y=2*9.6+160 | | 3x-8y-5z=15 | | 2a+7=a+28 | | -5y+18=-10+4y | | 18c-36=0 | | 2(2x+1)=-36 | | (X)(3x-5)=0 | | 29x-3=13y-17 | | -4x-6(1+3x)=-3x+32 | | 4x-5/3=3x-4/2 |